From User Education to Information Literacy: The Kwame Nkrumah University of Science Technology Library’s Experience - Ahenkorah-Marfo, Michael; Teye, Victor (Ghana Library Journal, 2009)
The user education programmes of the Kwame Nkrumah University of Science and Technology (KNUST) Library since the inception of the Library in 1961 were reviewed. Personal observation of the current user education programme was also made between 2007 and 2009. The study focused mainly on students both at undergraduate and postgraduate levels. It was observed that the user education programmes had gone through metamorphoses – from guided tours through video instruction and currently Information Literacy Skills programme (ILS), which is in the process of being implemented. The basic problem that has bedeviled all the user education programmes was found to be escalating student enrolment which renders the programmes ineffective. The study recommended among others: Sensitization of users, expansion of ICT infrastructure and eservices, and finally providing capacity at the college level to deal directly with students and faculty members to ensure that the ILS programme does not suffer from increased student enrolment